Preprosthetic Laser Assisted Mandibular Vestibuloplasty - Kacarska M.; Dimitrovski O.; Monevska D. Popovic (Balkan Stomatological Society, 2016)
A prosthetic treatment of the edentulous mandible can be very challenging. In cases with inadequate buccal depth, a necessary deepening of the oral vestibule can be achieved by surgically detaching the soft tissue attachments. A preprosthetic vestibuloplasty is usually done surgically by scalpel. With the permanent advancement of laser technology, a laser vestibuloplasty has become a preferred surgical procedure. The aim of this report was to present individuality of a mandible vestibuloplasty performed with Er.YAG laser.